Legitimacy in Mining Companies: The Effect of Asset Newness and Capital Expenditure on ESG Disclosure - Wiwit Hartanis; Ika Atma Kurniawanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Amid global sustainability pressures, mining companies are facing intense public scrutiny. Using an integrated framework of Legitimacy, Signaling, and Stakeholder theories, this study examines the influence of physical asset characteristics, specifically asset newness and capital expenditure (CAPEX), on Environmental, Social, and Governance (ESG) disclosure. Using a quantitative design, this study analyzes a purposive sample of 57 observations from mining companies for the period 2020-2024. Data are processed using fixed-effect panel data regression with robust standard errors. ESG disclosure is measured through content analysis based on the OJK index no. 51/POJK/03./2017. The results show that asset newness has a significant negative effect on ESG disclosure, confirming the phenomenon of "reverse legitimacy". This indicates that companies with obsolete assets use extensive disclosure as a defense mechanism to bridge the legitimacy gap and appease stakeholders. In contrast, CAPEX does not show a significant effect, implying that capital allocation in emerging markets is still focused on operational capacity and not yet oriented towards green technologies. This study concludes that ESG reporting often serves as a symbolic legitimacy tool rather than a proactive commitment. These findings encourage policymakers and investors to critically evaluate the true nature of corporate asset expansion. This study contributes to the literature by integrating physical asset metrics with the still very limited ESG disclosure and demonstrating the existence of the “reverse legitimacy” phenomenon and CAPEX divergence in the context of emerging economies.